(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: To determine the frequency and severity of depression in adolescents presenting in outpatient department of a tertiary care hospital. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at the Psychiatry OPD of Div. HQ Hospital Mirpur AJK from Sep. 2017 to Feb 2018. Materials and Methods: Data was collected by cluster sampling using the systematic random sampling technique. KADS for Depressive Illness was applied and data was then analyzed using SPSS 18. Results: In total (n=400) prevalence of depression is 12%, with 177 (44.3%) male and 223 (55.8%) female participants while 5.8%,5.0%,and 1.3% have mild, moderate and severe degree of depression respectively. Conclusion: The findings indicated that the clinician should determine a treatment plan that not only for assessment but also address the risk factors. Studies should be cost effective for treatment of depression as well as improving quality of life of sufferers.